Abstract 180: A Prospective, Single‐Center Study Appraising Aneurysm Embolization using the Balt Optima™ Coil System (APPLY Study) - Hunter J. King; Nicole Mercado; Siamak Bonabi; Antik Patel; Zeyad Khokhar; Nikil Swamy; Asif Taqi (Stroke: Vascular and Interventional Neurology)
Introduction Intracranial aneurysms, both ruptured and unruptured, pose a significant risk to the general population. Cases of unruptured intracranial aneurysms (UIA) are estimated to affect roughly 3% of the general population and aneurysmal subarachnoid hemorrhage (aSAH) have an incidence of 8 to 9 people per 100,000. With the advancement of endovascular coil devices, aneurysm embolization with coiling is becoming the more preferred treatment approach compared to craniotomy with microsurgical clipping. The purpose of this study was to assess the safety and efficacy of endovascular coiling using the novel Balt Optima™ Coil System. Methods This study was an investigator‐initiated, prospective, real‐world, single‐center, post‐market study conducted in Thousand Oaks, California. Between 2020 and 2023, thirty cerebral aneurysms were treated with at least 80% utilization of the Balt Optima™ Coil System. The subjects were followed for 6 months (‐4 months/+6 months). Data points were obtained at baseline, procedure, discharge or postoperative day 7, and 6 months follow‐up (‐4 months/+6 months). Primary outcomes were functional status recorded as modified Rankin scores (mRS) and radiographic occlusion rates documented as Raymond‐Roy scores. Serious adverse events including, but not limited to, groin hematoma, periprocedural stroke, intraoperative aneurysm rupture, coil herniation requiring stent placement, and mortality were recorded. Secondary outcomes included coil packing densities, minor complications, procedure duration, disposition after hospitalization, and antithrombotic medication adjustments. Results 30 intracranial aneurysms in 29 individual subjects were included in the study and were treated by a total of 4 neurointerventionalists with at least 80% use of the Balt Optima™ Coil System. One subject had two aneurysms which were treated at two separate occasions, and the subject was consented for both aneurysms to be included in the study. 60% of aneurysms were located along the right anterior circulation and vessels involved mirrored epidemiological data in the literature. 83% of subjects were female, and 50% of aneurysms presented as ruptured. All subjects had a baseline mRS 0‐2. 83% of aneurysms were treated with utilization of an assist device as well. At 6 months follow‐up (‐4 months/+6 months), 80% of subjects had mRS 0‐2. Of the 21 patients with 6 month (‐4 months/+6 months) follow‐up imaging, 15 (71%) had complete aneurysm occlusion (Raymond‐Roy score of 1) and 6 (29%) patients had residual aneurysm neck filling (Raymond‐Roy score of 2). One subject (3%) expired during the hospitalization due to complications unrelated to the aneurysm or coil system, and one subject (3%) was lost to follow‐up. One subject (3%) developed a groin hematoma, one subject (3%) had an intraoperative rupture with no significant clinical consequence, and two subjects (7%) experienced coil herniation requiring stent placement with no clinical sequelae. No subjects (0%) had periprocedural strokes. Conclusion This study demonstrates that the Balt Optima™ Coil System is safe and effective for endovascular treatment of both unruptured and ruptured intracranial aneurysms. Additional data is needed to validate these results and compare to other coil devices on the market.